Quantifying minimum site occupancy requirements of common forest tree species in northern New England, USA: Implications for stocking assessment - David Ray; Robert Seymour; Shawn Fraver; John-Pascal Berrill; Laura Kenefic; Nicole Rogers; Aaron Weiskittel (Forest Ecology and Management, 2024)

Pile burning after conifer removal from aspen stands affects tree mortality, regeneration, and understory recovery - John-Pascal Berrill; Christa M. Dagley; Yoon G. Kim; J. Morgan Varner (Forest Ecology and Management, 2024)

Early Responses to Crown Modification of California Black Oak Sprouts Initiated by High-Severity Wildfire - Martin Ritchie; John-Pascal Berrill; Ethan Hammett; Jonathan W Long (Journal of Forestry, 2024)
Hardwoods resprouting after wildfire or cutting develop as multistemmed clumps that gradually self-thin over time. There is increasing interest in thinning of sprouting species to accelerate the formation of tree characteristics important to indigenous cultural practices and wildlife such as large-diameter stems, large branches, broad crowns, and acorn production. We compared responses to three thinning treatments applied to black oak (Quercus kelloggii) resprouting after high-severity wildfire throughout northern California, USA. Basal area increment of the dominant stem was greatest after only one stem was retained, intermediate after three stems were retained, and lowest within unthinned oaks. Unwanted resprouting in response to the thinning was minimized by retaining three stems. Acorn production tended to increase as time elapsed since the fire (i.e., larger, older sprouts) but varied among sites and was noted as early as six years after fire at one site. More study is needed to test for the effects of thinning timing and intensity on the acceleration of acorn production as well as stem, branch, and crown size development over time.

Relative Density as a Standardizing Metric for the Development of Size-Density Management Charts - David Ray; Robert Seymour; Shawn Fraver; John-Pascal Berrill; Laura Kenefic; Nicole Rogers; Aaron Weiskittel (Journal of Forestry, 2023)
Stand density management is central to achieving diverse silvicultural objectives. Decision-support tools in this domain range from expert opinion to sophisticated computer models that vary by forest type, region, and organization. The graphical frameworks represented by density management diagrams (DMDs) and stocking guides (SGs), collectively called size-density management charts (SDMCs), are well established and balance quantitative rigor with user accessibility. Regional differences in species composition and site quality are known to influence maximum size-density relationships, historically limiting the development of reliable charts. Advances in statistical modeling and data availability are overcoming this issue and should encourage more widespread use. We briefly review the history of SDMCs and propose the adoption of relative density based on stand density index as a logical metric for linking the DMD and SG formats. Examples of SDMC construction and use are illustrated for spruce-fir stands in Maine, USA. Study Implications: Recognition of the importance of stand density management has increased in recent years owing to its potential to address threats such as susceptibility to catastrophic wildfires and forest health issues exacerbated by environmental stress. Natural resource managers will benefit from adopting a language around density management that is both biologically grounded and consistent. A relative density framework is compatible with the two primary types of size-density management charts and thus meets this objective well. Relative density provides an ideal launching point for articulating levels of stand density, or stocking, to meet diverse management objectives determined under relevant socioecological constraints.

Tree-level responses to commercial thinning in spruce-fir forests across northern Maine, USA - Bishnu Hari Wagle; Aaron R. Weiskittel; John-Pascal Berrill; Anil R. Kizha; Anthony W. D'Amato; David Marshall (Forest Ecology and Management, 2023)

Performance and genetic analysis of coast redwood cultivars for afforestation of converted grassland in California - William M. Morrison; Andrew D. Armstrong; Lynn A. Webb; Christa M. Dagley; Kathleen G. Cahill; John-Pascal Berrill (New Forests, 2022)

Development of Redwood Regeneration after Conifer Partial Harvest and Hardwood Management - John-Pascal Berrill; Lynn A Webb; Kristy L DeYoung; Christa M Dagley; Christopher G Bodle; Sean M Simpson (Forest Science, 2021)
Harvesting of commercial conifer species from conifer-hardwood mixtures can leave residual stands dominated by hardwoods. Removing unwanted hardwoods by cutting or herbicide makes growing space available to residual trees and regeneration and can restore conifer dominance. Forest managers of north coastal California need guidance on how such treatments affect subsequent growth of planted redwoods (Sequoia sempervirens [D. Don.] Endl.) or natural regeneration, as well as proliferation of undesirable species. Our observational study reconstructed growth of 108 regenerating redwoods in 26 treated stands. Residual stand density was the main driver of height and diameter growth in the new cohort of redwoods, irrespective of whether hardwoods were cut or received herbicide frill treatment (prevents resprouting). At lower residual stand densities, there were higher densities of natural regeneration (ingrowth) of conifers and hardwoods, which affected diameter at breast height (dbh) growth of regenerating redwoods. After heavier cutting of hardwoods, this ingrowth comprised a greater proportion of unwanted hardwood regeneration. Therefore, frill treatment is recommended when the objective of management is to reduce hardwood stocking and regeneration. Combining partial harvesting of conifers with cutting or frill treatment of hardwood is another option that reduces stand density to promote height and dbh growth of regenerating redwoods.

Understory light predicts stump sprout growth in mixed multiaged stands in north coastal California - John-Pascal Berrill; Kurt Schneider; Christa M. Dagley; Lynn A. Webb (New Forests, 2018)